2019
DOI: 10.1177/0972063419868561
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Largely Unregulated Private Health Sector Impact the Indian Mass?

Abstract: Private hospitals in India are least monitored by the government, which leads to violation of the roles and responsibility they have to offer for the community. Indeed, it is a more serious issue in a country like India where people are forced below poverty line (BPL) after every hospitalization. Of the four different models of health expenditure, India and, in fact, many developing countries follow the out-of-pocket (OOP) expenditure model rampantly. This is very evident from the recent working article (2015)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The process of procurement and sale of the drugs in the private sector remains largely unregulated and contributes to significant OOP and catastrophic expenditure. 27,28 Further work is needed to better understand the medicine supply chain and identify the steps leading to prices becoming unaffordable for patients. The priority list of oncologists from India had 85% concordance with that of other LMICs, highlighting the wide consensus on relevance of these drugs in similar settings.…”
Section: Discussionmentioning
confidence: 99%
“…The process of procurement and sale of the drugs in the private sector remains largely unregulated and contributes to significant OOP and catastrophic expenditure. 27,28 Further work is needed to better understand the medicine supply chain and identify the steps leading to prices becoming unaffordable for patients. The priority list of oncologists from India had 85% concordance with that of other LMICs, highlighting the wide consensus on relevance of these drugs in similar settings.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Saudi Arabia, [18] identified six components that influences choice of hospital, in which perceived quality of medical care was the most prominent one. Several studies [19][20][21] [ 22,23] The study also reports influence of online reviews on brand value of the hospitals. Unlike traditional hospitals, there is need to be vigilant on the e-WOM in long run brand building process.…”
Section: Discussionmentioning
confidence: 99%
“…However, in India, the need for these national reforms, i.e. PMSSY and AB-PMJAY is generally attributed to the inefficient use of scarce resources, high out of pocket expenditure (OOPE) on health care (Nandi et al , 2017) inadequate and cost-ineffective services, poor execution of health schemes, low funding for primary and secondary care, major spending on tertiary care, unavailability of health services, geographical location and financial exploitation by the unregulated private sector hospitals (Dehury et al , 2019). Even though the Indian Government is investing heavily, it appears that implementation and monitoring issues have impeded these national schemes.…”
Section: Impact Of Lack Of Health-care Leadership Capacity On Public ...mentioning
confidence: 99%